Appendicitis Perforasi: Laporan Kasus - Ma’arif, Andi Isyraf; Latief, Shofiyah; Mesak, Mesak (Innovative: Journal Of Social Science Research, 2025)
Background: Appendicitis is inflammation of the vermiform appendix which can develop into serious complications if not treated immediately. The prevalence of appendicitis in Indonesia is relatively high, with an incidence rate of 0.05%. The most common treatment for appendicitis is appendectomy, which can be performed using open or laparoscopic surgical techniques. Methods This case involved a 20 year old man who came in with complaints of lower right abdominal pain, which had become increasingly severe in the last two days. Physical examination shows tenderness and typical signs of appendicitis such as positive McBurny Sign and Rovsing Sign. The diagnosis of perforated appendicitis was confirmed after an ultrasound examination. The surgical procedure was carried out by appendectomy laparotomy. Results: The patient underwent a perforated appendectomy procedure. During the surgical process, the appendix is ​​found to be perforated, which can cause peritonitis or abscess if not treated immediately. After the sanitation procedure, the patient is intensively treated with antibiotics and intravenous fluids. Conclusion: Appendicitis perforation is a condition that requires quick treatment to avoid more serious complications such as peritonitis and abscess. Correct diagnosis and prompt treatment are essential to reduce the risk of complications and speed up the patient's recovery process.